A LITERATURE REVIEW POTENTIAL DEVELOPMENT OF HALAL INDUSTRY IN INDONESIA - Izzuddin, Muhmmad; Adinugraha, Hendri Hermawan (Likuid Jurnal Ekonomi Industri Halal, 2022)
This study aims to explain the potential of the Halal Industry in Indonesia. This research also identifies opportunities and challenges in its development. The method used in this research is descriptive-qualitative method with a phenomenological approach. The data obtained were analyzed using qualitative analysis through data reduction, categorization and verification. This study found that Indonesia has the potential to develop the Halal Industry in various sectors, especially halal food, halal tourism, halal fashion, halal pharmacy and halal cosmetics. The development of the Halal Industry also has the potential to increase national economic growth. However, Indonesia must face various challenges such as low awareness of halal, low competitiveness of local products and problems in implementing the Halal Product Assurance Regulation.Â